Clarice Lispector, uma plagiadora de si mesma: republicação nas crônicas do Jornal do Brasil (1967-1973) - Souza, Thais Torres de (2008)
During the seven years when Clarice Lispector published her chronicles in the newspaper Jornal do Brasil (1967 1973), she republished several novels from books which had been put into print prior to her work in the newspaper, as well as first versions of texts that would be later re-edited in other communication vehicles. This aim of this paper is to outline those publications and analyze the effects from this constant self-plagiarism on Lispectors work in the newspapers and books. We establish that these repetitions are due, on one hand, to the authors negligence regarding her activities in the newspaper, once we assume that there is no effort from Clarice to produce original chronicles. On the other hand, she seemed to be more interested on publishing some texts than others, what would point some kind of explicit literary choice and a need for reaffirming and re-reading her own texts by republishing them. The analysis of the changes performed between the publications reveals what reformulations were made and, in the case of the texts which had suffered almost no changes, how does this fact establish an interest on reaffirming their importance, by exposing them to different audiences. We believe that the \"self-plagiarism\", by revealing the author\'s quest for the comprehension of her own work, points out to the major problematics of Clarician\'s creative processes.